Robotic exploration of the solar system Part 3: wows and woes, 1997-2003 - Ulivi, Paolo (Springer Praxis Books, 2012)
In Robotic Exploration of the Solar System, Paolo Ulivi and David Harland provide a comprehensive account of the design and managment of deep-space missions, the spacecraft involved - some flown, others not - their instruments, and their scientific results. This third volume in the series covers launches in the period 1997 to 2003 and features:- a chapter entirely devoted to the Cassini-Huygens mission to Saturn; coverage of planetary missions of the period, including the Deep Space 1 mission and the Stardust and Hayabusa sample returns from comets and asteroids; extensive coverage of Mars exploration, the failed 1999 missions, Mars Odyssey, Mars Express, and the twin rovers Spirit and Opportunity.The story will continue in Part 4.